Analysis of Trade Law in Modern Business Practices in Indonesia - Nurtresna, Robby; Hidayatulloh, Syarif; Maulana, Anas; Lutvansyach, Achmad; Hutagalung, Henni (LAW FACULTY UNISSULA, 2024)
International trade allows the exchange of goods and services between countries, which optimizes profits and expands markets, and also plays an important role in driving global economic growth. However, international trade raises various new problems due to differences in legal systems between countries, such as Continental European law in Indonesia and Anglo-Saxon law in Singapore and various other legal systems adopted by countries in the world. This is to ensure smooth cross-border transactions, a deep understanding of commercial law is needed because these differences can also affect the formation and completion of contracts. The purpose of this study is to review commercial law as a whole, including definitions, sources, scope, and problems that often arise in practice, as well as solutions to these problems. This study uses a normative legal method with secondary data and the data is analyzed using qualitative descriptive techniques. The hope of this study is to improve our understanding of how commercial law is applied in international trade, and also how the law functions to ensure legal security and this also protects the rights of the parties involved. The results show that commercial law functions as a foundation that regulates the relationship between parties involved in economic activities, namely companies, consumers, and also the government. This trade law ensures that transactions are carried out fairly and in accordance with applicable provisions, protects the rights of the parties involved, and this fosters trust in the trade system itself.